Improving the Student Performance Using Think-Pair-Share for Operating System - Pardeshi, Komal R. (Journal of Engineering Education Transformations, 2016)
It is observed that while delivering a lecture in class it is good to ask questions to check understanding of the students, but not all students are able to answer the questions. It is also observe that whenever instructor asks a particular student for answer, other students stop processing for their answer. To keep all the students actively engaged in the class one of the active teaching-learning strategies that is Think-Pair-Share (TPS) has been implemented. TPS is a classroom-based active learning strategy, in which students work on a problem posed by the instructor, first individually, then in pairs, and finally as a class wide discussion. As the Operating System is core subject of computer science engineering, therefore the activity was conducted for the third year students to improve students' conceptual understanding. In this paper, one group Pre-Test and Post-Test model is considered. The experimental results and students feedback related to the activity are also presented.